Abnormal Galactosylated–Glycans recognized by Bandeiraea Simplicifolia Lectin I in saliva of patients with breast Cancer - Yang, Jiajun; Liu, Xiawei; Shu, Jian; Hou, Yao; Chen, Mengting; Yu, Hanjie; Ma, Tianran; Du, Haoqi; Zhang, Jiaxu; Qiao, Yan; He, Jianjun; Niu, Lili; et al. (Glycoconjugate journal, 2020)
Currently, the definitive diagnosis in breast cancer requires biopsy and histopathology, such the most effective markers are tissue-based. However, the advantages of saliva in collection and storage make it possible for assessing human pathology and contributing to the development of cancer-related biomarkers for clinical application. The present study validated alteration of salivary protein glycopatterns recognized by Bandeiraea simplicifolia lectin I (BS-I) in the saliva of patients with breast diseases using saliva microarrays, and the N/O-glycan profiles of their salivary glycoproteins isolated by the BS-I-magnetic particle conjugates from 259 female subjects (66 healthy volunteers (HV), 65 benign breast cyst or tumor patients (BB), 66 patients with breast cancer in stage I (BC-I) and 62 patients with breast cancer in stage II (BC-II)) were analyzed by MALDI-TOF/TOF-MS. The results showed that the expression level of galactosylated glycans recognized by BS-I was significantly increased in patients with breast cancer compared with HV ( p < 0.05). Totally, there were 11/10, 10/19, 7/24 and 7/9 galactosylated N-/O-linked glycans were identified and annotated from the pooled salivary samples of HV, BB, BC-I and BC-II, respectively. One galactosylated N-glycan peak (m/z 2773.977), and 4 galactosylated O-glycan peaks (m/z 868.295, 882.243, 884.270 and 1030.348) were found only in BC-I. These findings could provide pivotal information on galactosylated N/O-linked glycans related to breast cancer, and promote the study of biomarkers for early-stage breast cancer based on precise alterations of galactosylated N/O-glycans in saliva.